An Evaluation of Parasitic Load and Symptom Profile in Tungiasis: A Study of Endemic Communities of Ethiopia - DR.SURESH KUMAR.P.NAIR; NIKHIL.S; DR.TEFERI ESHETU (International Journal of Pharma and Bio Sciences, 2018)
Tungiasis or locally known as Mujali is a disease of neglected poor communities and it has become a nuisance in many endemic areas. This disease is caused by an ectoparasite Tunga penetrans that belongs to Family Hectopsyllidae, Order Siphonaptera and Class Insecta. The gravid female produces 100 to 200 eggs and these will hatch out within 6 days. There are two instar phases and within 15 days it becomes adult flea. Female adult flea penetrates the epidermis. This causes itching, pain and edema in the area of penetration. Often many insects will penetrate at the same time and many lesions can be noticed in an individual. Repeated infections occur especially in toes and this may cause deformities of the toes. The studied communities were located in eight villages of South and South west part of Ethiopia, Wolaita sodo and Jimma area, respectively. This is a cross-sectional study in which a total of randomly selected 2795 subjects were included. All the selected subjects were studied using a standard questionnaire with interview and clinical analysis. The response rate was 100%. The prevalence rate of tungiasis was 24% in Wolaita sodo and 15% in Jimma. These areas were endemic with varying degrees of symptoms and severity. The lesions were most commonly located in different parts of the leg especially on toes and sole. The most favorite locations were sole (35 to 42%), periungual region (30 to 34%) and subungual region (25 to 33%). The most common symptoms noticed include itching and pain (58.7% to 82.1%) with a parasitic load of 1-4 (50%), 5-9 (27%), 10-19 (15.4%), 20-49 (5.6%), and > 50 (2%). Traditional treatment with cow dung often leads to secondary infections and worsens the condition. The studied communities were with poor socio-economic status. This disease is often noticed in populations with poor socio-economic conditions.